ESTABLISHMENT OF CHILDREN'S TOLERANCE ATTITUDE WITH THE TRADITIONAL GOBAK SODOR APPROACH - Mochammad Syihabbudin; Kartika Nur Umami (Nurul Jadid University, 2021)
Today's children are required to always adapt to the times so that local culture begins to disappear among children. Technological advances have an impact on shifting values, attitudes, and culture, one of which is tolerance. Education has an important role in designing interesting learning because education is the most effective place in providing education to improve knowledge, attitudes, and love of culture. One of the causes for the fading of children's tolerance is the lack of understanding and attention from educational institutions to always educate the importance of learning design in shaping children's tolerance attitudes. The purpose of this study was to analyze the design of learning by utilizing teaching materials the gobak sodor game approach can form an attitude of tolerance or not. This study uses qualitative methods and data collection steps as follows; 1) Planning Stage, 2) Field research stage, 3) Data analysis stage, 4) Data reduction, 5) Display and 6) Data verification. While the results of the study in the form of the tolerance aspect got a final score of 87.5 with a good category and the traditional game aspect of Gobak Sodor got a final score of 85 with a good category.